Intraosseous infantile myofibroma of the mandible - Nirvikalpa, Natarajan (Medknow Publications & Media Pvt Ltd, 2011)
The myofibroma, especially the intraosseous variety, is an uncommon benign tumor that occurs primarily in children younger than 3 years of age. Since 1966, less than 40 cases of solitary myofibromas of the mandible have been reported in the literature. Myofibroblasts and spindle cells are predominantly found in this benign lesion. These cells are also commonly found in many lesions due to which great difficulty can be encountered in the diagnosis. A rare case of the intraosseous variety of an infantile myofibroma of the mandible diagnosed in a 10-month-old child has been reported. The tumor was completely excised via an intraoral approach and no recurrence has been noted 15 months postoperatively. A brief review of the differential diagnosis of this lesion in terms of its clinicopathologic, histologic, and immunohistochemical features is also discussed.